A cubane-type manganese complex with H2O oxidation capabilities - Watson, Graeme; Schmitt, Wolfgang; Venkatesan, Munuswamy (My University, 2020)
We report the synthesis and characterisation of [Mn8K2O4(OH)2((CH3)3CCOO)16(CH3CN)2] whose cluster core shares some features with the oxygen evolving complex (OEC), the natural water oxidation catalyst. Importantly, this complex provides a bio-inspired complex that promotes catalytic H2O oxidation at neutral pH value.
PUBLISHED